STRATEGI PENERAPAN PENDIDIKAN KARAKTER PEDULI LINGKUNGAN, KERJASAMA DAN TANGGUNG JAWAB DALAM PROGRAM ADIWIYATA SEKOLAH DASAR - Neti, Neti; Marzuki, Marzuki; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe problem in this study is the number of activities that damage the environment, the quality of the environment is now declining due to exploitative actions against nature excessive regardless of the carrying capacity of the environment and its ecological function. For example, excessive deforestation can lead to floods and landslides, the use of dynamite for fishing can damage coral reefs. Therefore, this study aims to describe the planning, implementation, and supporting factors for the Implementation of Character Education for the Environment, Cooperation, and Responsibility through the Adiwiyata Program at State Elementary School 28 North Pontianak. This research uses direct observation and interview method, which become the subject of this research is the students of VC class of State Elementary School 28 North Pontianak. Based on research conducted during four meetings, it was found that by implementing adiwiyata program in VC class of State Elementary School 28 North Pontianak can instill environmental caring character, cooperation and responsibility to students in VC class of State Elementary School 28 North Pontianak class with highest percentage reaching 100% on environmental care aspects. On the aspect of cooperation reached 81% percentage, then on the aspect of responsibility reached 93% percentage. Based on the data obtained, it can be concluded that the application of character education for environment, cooperation and responsibility can be instilled through adiwiyata program.Â Keywords: Character, Environmental care, Cooperation, Responsibility, Adiwiyata.Â